2013
DOI: 10.1049/iet-spr.2011.0422
|View full text |Cite
|
Sign up to set email alerts
|

Further investigation on time‐domain maximum likelihood estimation of chirp signal parameters

Abstract: The time-domain maximum likelihood estimation of chirp signal parameters is investigated in this study. Three amplitude weighted phase-based estimators and two phase-unwrapping algorithms, that is, phase prediction and unwrapping algorithm (PP-UA) and differenced-phase prediction and unwrapping algorithm (DPP-UA) were proposed. The DPP-UA and PP-UA have their merits and drawbacks. The authors combine the merits of these two methods and propose a new phaseunwrapping algorithm, which outperforms PP-UA and DPP-UA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…There have also been several papers covering the EPS estimation issue, see, e.g. [35–41] for more comprehensive understanding.…”
Section: Novel Estimation Algorithm Via Ipccmentioning
confidence: 99%
“…There have also been several papers covering the EPS estimation issue, see, e.g. [35–41] for more comprehensive understanding.…”
Section: Novel Estimation Algorithm Via Ipccmentioning
confidence: 99%
“…are obtained from the principal values, and no PU is performed. The choice of N 1 is very important, and it is shown that N 1 is SNR related [62]. Because in a real implementation we have no a priori knowledge of the input SNR, a fixed N 1 is a reasonable choice.…”
Section: Compound Time-frequency Domain Parameter Estimationmentioning
confidence: 99%
“…Defining the initialisation time as N 1 , the data phases normal∠DPMmnormal′false[rmnormal′false(kfalse),1false] for k = 1, …, N 1 are obtained from the principal values, and no PU is performed. The choice of N 1 is very important, and it is shown that N 1 is SNR related [62]. Because in a real implementation we have no a priori knowledge of the input SNR, a fixed N 1 is a reasonable choice.…”
Section: Compound Time‐frequency Domain Parameter Estimationmentioning
confidence: 99%
“…second‐order polynomial phase signals (PPSs), arise in many signal processing applications. The most notable applications are in radar, sonar, and wireless communications [1–5]. In recent years, a variety of algorithms have been proposed to estimate the chirp parameters.…”
Section: Introductionmentioning
confidence: 99%